2010
DOI: 10.1007/s10549-010-1216-1
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy characteristics are important predictors of primary prophylactic CSF administration in older patients with breast cancer

Abstract: Chemotherapy is vital for breast cancer management, but early onset toxicities like neutropenia hinder its administration. Primary prophylactic (PP) use of colony- stimulating factors (CSF) helps prevent neutropenia and ensures successful chemotherapy completion. Nevertheless, lack of specific guidelines for CSF administration in older patients has lead to unexplained geographic and racial, and counter-intuitive clinical variations in CSF administration. This study examined the reasons for these variations and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…A previous study performed by one of the authors found that once chemotherapy characteristics like type of drug, number of drugs used per cycle, and duration between cycles are controlled for, age and comorbidity index were no longer correlated with CSF use. 34 The reduction in CSF use with increase in age and comorbidity index is similar to the results from other studies, which did not control for chemotherapy characteristics. 29,31,35 Despite controlling for clinical history, tumor, and treatment characteristics, sociodemographic variations persisted.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…A previous study performed by one of the authors found that once chemotherapy characteristics like type of drug, number of drugs used per cycle, and duration between cycles are controlled for, age and comorbidity index were no longer correlated with CSF use. 34 The reduction in CSF use with increase in age and comorbidity index is similar to the results from other studies, which did not control for chemotherapy characteristics. 29,31,35 Despite controlling for clinical history, tumor, and treatment characteristics, sociodemographic variations persisted.…”
Section: Discussionsupporting
confidence: 86%
“…Both these differences have also been observed in older national studies examining the utilization of HGF in the United States, thereby raising concerns about the persistence of these variations and disparities over time. 29,[34][35] Regional variations are often an indication of cumulative differences in physician preferences and practice patterns between regions. Studies have documented that CSFs are frequently used in scenarios where their use is not recommended by evidencebased guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of different myelosuppressive chemotherapy regimens have proven to be efficacious and safe in clinical trials, and are commonly used today in US clinical practice [1,2]. Reductions from published trial-based or reference ''standard'' dose of chemotherapy among patients with ESBC may occur due to a variety of factors-especially advanced age and hematological adverse events, such as neutropenia and related infections-and are generally believed to result in an increased risk of disease progression and poorer overall survival [3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 describes each characteristic and the corresponding variable. The association of these characteristics with primary prophylactic G-CSF administration has been explored by the authors previously [46]. Since administration of primary prophylactic G-CSF and risk of neutropenia are associated with the initiation of chemotherapy, all clinical history variables (e.g., modified Charlson comorbidity index, past history of any cancer, history of infections, antibiotic use, and hospitalizations) were measured with respect to initiation of chemotherapy.…”
Section: Potential Confounding Variablesmentioning
confidence: 99%